Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1) \(\left(x-1\right)\left(\frac{1}{10}+\frac{1}{11}+\frac{1}{12}-\frac{1}{13}\right)=0\)
mà \(\frac{1}{10}+\frac{1}{11}+\frac{1}{12}-\frac{1}{13}\ne0\)
\(\Rightarrow x-1=0\Leftrightarrow x=1\)
2) \(\frac{x-1}{99}-1+\frac{x-2}{98}-1+\frac{x-5}{95}-1=\frac{1}{99}+\frac{1}{98}+\frac{1}{95}\)
\(\frac{x-100}{99}+\frac{x-100}{98}+\frac{x-100}{95}=\frac{1}{99}+\frac{1}{98}+\frac{1}{95}\)
\(\left(x-100\right)\left(\frac{1}{99}+\frac{1}{98}+\frac{1}{95}\right)=\frac{1}{99}+\frac{1}{98}+\frac{1}{95}\)
x - 100 = 1
x = 101
\(\frac{x+1}{99}+\frac{x+2}{98}+\frac{x+3}{97}+\frac{x+4}{96}=-4\)
\(\Rightarrow\left(\frac{x+1}{99}+1\right)+\left(\frac{x+2}{98}+1\right)+\left(\frac{x+3}{97}+1\right)+\left(\frac{x+4}{96}+1\right)=0\)
\(\Rightarrow\frac{x+100}{99}+\frac{x+100}{98}+\frac{x+100}{97}+\frac{x+100}{99}=0\)
\(\Rightarrow\left(x+100\right)\left(\frac{1}{99}+\frac{1}{98}+\frac{1}{97}+\frac{1}{98}\right)=0\)
\(\Rightarrow x+100=0\)
\(\Rightarrow x=-100\)
a) \(\left(4x-13\right)^4+4^3=145\)
\(\Rightarrow\left(4x-13\right)^4+64=145\)
\(\Rightarrow\left(4x-13\right)^4=81\)
\(\Rightarrow4x-13=\pm3\)
+) \(4x-13=3\)
\(\Rightarrow4x=16\)
\(\Rightarrow x=4\)
+) \(4x-13=-3\)
\(\Rightarrow4x=10\)
\(\Rightarrow x=\frac{5}{2}\)
Vậy \(x=4\) hoặc \(x=\frac{5}{2}\)
b) \(3^{x+2}-3^x=72\)
\(\Rightarrow3^x.3^2-3^x=72\)
\(\Rightarrow3^x.\left(3^2-1\right)=72\)
\(\Rightarrow3^x.8=72\)
\(\Rightarrow3^x=9\)
\(\Rightarrow3^x=3^2\)
\(\Rightarrow x=2\)
Vậy \(x=2\)
c) \(2^{x+2}-2^{x-1}=224\)
\(\Rightarrow2^{x-1+3}-2^{x-1}=224\)
\(\Rightarrow2^{x-1}.2^3-2^{x-1}=224\)
\(\Rightarrow2^{x-1}.\left(2^3-1\right)=224\)
\(\Rightarrow2^{x-1}.7=224\)
\(\Rightarrow2^{x-1}=32\)
\(\Rightarrow2^{x-1}=2^5\)
\(\Rightarrow x-1=5\)
\(\Rightarrow x=6\)
Vậy x = 6
a, \(x:3\frac{1}{15}=1\frac{1}{2}\)
\(\Rightarrow x=1\frac{1}{2}\cdot3\frac{1}{15}\)
\(\Rightarrow x=\frac{3}{2}\cdot\frac{46}{15}=\frac{3\cdot46}{2\cdot15}=\frac{1\cdot23}{1\cdot5}=\frac{23}{5}=4\frac{3}{5}\)
\(b)x\cdot\frac{15}{28}=\frac{3}{20}\)
\(\Rightarrow x=\frac{3}{20}:\frac{15}{28}=\frac{3}{20}\cdot\frac{28}{15}=\frac{1}{5}\cdot\frac{7}{5}=\frac{7}{25}\)
Tự làm nốt câu cuối :>
a) x - 13+x = -24-7 + x
2x-13 = -31 +x
2x-x = -31+13
x = -18
b) 12.20 = 15x
240 = 15x
x = 16
c) 42(-5) = 14x
-210 = 14x
x = -15
\(2x+x:3-20=13.\left(98-26.3\right)\)
\(\Rightarrow2x+\dfrac{1}{3}x-20=13.\left(98-78\right)\)
\(\Rightarrow\dfrac{7}{3}x=13.20+20\)
\(\Rightarrow\dfrac{7}{3}x=20.\left(13+1\right)\)
\(\Rightarrow\dfrac{7}{3}x=20.14\Rightarrow\dfrac{7}{3}x=280\)
\(\Rightarrow x=280:\dfrac{7}{3}=120\)
Chúc bạn học tốt!!!
\(2x+x:3-20=13(98-26.3)\)
\(2x+x:3-20=13.20\)
\(2x+x:3-20=260\)
\(2x+x:3=280\)
\(x\left(2+\dfrac{1}{3}\right)=280\)
\(\dfrac{7}{3}x=280\)
\(x=120\)